2008
DOI: 10.1371/journal.pone.0002331
|View full text |Cite
|
Sign up to set email alerts
|

Introduced Mammalian Predators Induce Behavioural Changes in Parental Care in an Endemic New Zealand Bird

Abstract: The introduction of predatory mammals to oceanic islands has led to the extinction of many endemic birds. Although introduced predators should favour changes that reduce predation risk in surviving bird species, the ability of island birds to respond to such novel changes remains unstudied. We tested whether novel predation risk imposed by introduced mammalian predators has altered the parental behaviour of the endemic New Zealand bellbird (Anthornis melanura). We examined parental behaviour of bellbirds at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
70
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 45 publications
5
70
1
Order By: Relevance
“…Provisioning rates declined for all 10 bird species in two different geographical areas when vocalizations of a local nest predator were broadcast near the nest, compared with both temporal and model controls ( figure 2a,b). This result alone is not surprising, as several studies have shown that parents reduce provisioning rates in the face of increased predation risk [7][8][9][10][11]. More importantly, our results show that the amount by which parents decreased provisioning (i.e.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Provisioning rates declined for all 10 bird species in two different geographical areas when vocalizations of a local nest predator were broadcast near the nest, compared with both temporal and model controls ( figure 2a,b). This result alone is not surprising, as several studies have shown that parents reduce provisioning rates in the face of increased predation risk [7][8][9][10][11]. More importantly, our results show that the amount by which parents decreased provisioning (i.e.…”
Section: Discussionsupporting
confidence: 78%
“…Increased parental food delivery rates to offspring are a clear benefit that can influence offspring quality [4,5], but can incur costs by attracting predators and increasing the risk of offspring predation [6]. Temporal and spatial variation in predation risk should favour the evolution of behavioural plasticity, whereby parents reduce nestling provisioning rates when faced with an immediate increase in predation risk [7][8][9][10][11]. Yet, while such plasticity appears to be adaptive, withholding care also has costs, leading to the question of how much parents should reduce care when predators are present [1,12].…”
Section: Introductionmentioning
confidence: 99%
“…This agrees with previous studies on the topic (e.g. Eggers et al 2005Eggers et al , 2008Massaro et al 2008;Peluc et al 2008;Zanette et al 2011;Ghalambor et al 2013;Hua et al 2014) and also with the reduction in nest visits observed for female Blackbirds during the incubation stage (Ibáñez-Á lamo and Soler 2012). However, adult Blackbirds did not show an increase in latency time due to a high perceived predation risk (prediction 1b).…”
Section: Discussionsupporting
confidence: 93%
“…This different detectability between sexes also affects parental provisioning in a context of adult-directed predation risk (Grunst et al 2015), suggesting that it could also alter sex-specific parental care when the threat is directed at their offspring. This sexual perspective has been partially investigated during incubation Martin 2000, 2002;Fontaine and Martin 2006;Massaro et al 2008), but those studies have focused primarily on different approaches for each sex due to different sexual roles. For example, it is common to measure nest visit rate during incubation for males and the incubation bout length for females, since in many species, males feed the incubating female, which is the only sex that incubates (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation